Produktivitas vs Kesehatan Mental: Peran Beban Kerja dan Dukungan Sosial Terhadap Burnout - Abdillah Iskandar, Imam Abdillah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Burnout is a condition of physical, emotional, and mental exhaustion frequently experienced by employees as a result of excessive job demands and insufficient social support in the workplace. This phenomenon is particularly relevant in industrial regions such as Karawang Regency, where employees are exposed to high work intensity and pressure. This study aimed to analyze the effects of workload and social support on burnout levels among employees in Karawang Regency. A quantitative approach was employed using a causal research design with multiple linear regression analysis. The study involved 397 employees selected through snowball sampling. The research instruments used had been tested and demonstrated satisfactory validity and reliability, including the CarMen-Q to measure workload, the Multidimensional Scale of Perceived Social Support (MSPSS) to assess social support, and the Maslach–Trisni Burnout Inventory (M-TBI) to measure burnout. The results of the simultaneous analysis indicated that workload and social support jointly had a significant effect on burnout, as evidenced by an F-test significance value of 0.000 (p < 0.05). Partially, workload was found to have a positive and significant effect on burnout, whereas social support had a negative and significant effect. These findings indicate that higher workload levels tend to increase burnout, while adequate social support serves as a protective factor in reducing burnout. This study underscores the importance of effective workload management and the creation of a supportive work environment to maintain employees’ mental health. Strong social support from family members, friends, and coworkers has been shown to reduce the risk of burnout, particularly in high-pressure work settings such as those found in Karawang Regency.